Biomass-derived N, S self-doped activated carbon embedded MnO2 as cathode for supercapacitor. (19th September 2022) - Dhinesh, S.; Priyadharshini, M.; Pazhanivel, T.; Gobi, R.
ABSTRACT: Despite its good electrochemical process, the crystal structure of transition metal oxide often suffers slow rate performance and significant volume expansion resulting in high resistance leading to structural instability. Because of the stated phenomenon, metal oxide ensued in capacity degradation and narrow down the overall efficiency of energy device. To nullify the effect, , we acquired a simple procedure to synthesis biomass-derived N, S doped Activated carbon and composited with transition metal (Mn) oxide. Systematic investigation was carried out to analyse its physiochemical and electrochemical properties. The prepared composite shows enhanced specific capacitance ( 700 F g −1 ) than bare, long-run cyclic stability (86% over 3000 cycles). AC matrix benefits a facile charge transfer and buffered mechanical stress during intercalation and deintercalation of ions in nanocomposite. The enhanced electrochemical performance in a wide voltage window and simple synthesis condition suggest biomass-derived N, S doped AC/MnO2 nanocomposite a potential candidate for supercapacitor application. Graphical Abstract: uf0001